2001
DOI: 10.1182/blood.v97.10.3117
|View full text |Cite
|
Sign up to set email alerts
|

Model for a factor IX activation complex on blood platelets: dimeric conformation of factor XIa is essential

Abstract: Human coagulation factor XI (FXI) is a plasma serine protease composed of 2 identical 80-kd polypeptides connected by a disulfide bond. This dimeric structure is unique among blood coagulation enzymes. The hypothesis was tested that dimeric conformation is required for normal FXI function by generating a monomeric version of FXI (FXI/PKA4) and comparing it to wild-type FXI in assays requiring factor IX activation by activated FXI (FXIa). FXI/PKA4 was made by replacing the FXI A4 domain with the A4 domain from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
75
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 36 publications
(66 reference statements)
3
75
2
Order By: Relevance
“…In a current model of FXI activation, the circulating FXI dimer is complexed with either HMWK (17)(18)(19) or prothrombin (18,20), both of which bind to the A1 domain of FXI (21).…”
mentioning
confidence: 99%
“…In a current model of FXI activation, the circulating FXI dimer is complexed with either HMWK (17)(18)(19) or prothrombin (18,20), both of which bind to the A1 domain of FXI (21).…”
mentioning
confidence: 99%
“…However, recent work suggests that the physiologic environment for this reaction may be the surface of activated platelets (46,49,50). In this environment, the dimeric structure of factor XI is necessary for normal FIX activation, possibly because one polypeptide of the dimer is required for binding to the platelet, whereas the other interacts with FIX (46,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shed light on this conundrum. It has been shown that HK facilitates FXI binding to the surface of activated platelets, where it is rapidly activated to FXIa (18,20,43). Prothrombin may serve as a substitute for HK in this role, providing a plausible explanation as to why HK-deficient humans do not bleed (19).…”
Section: Resultsmentioning
confidence: 99%
“…These findings, in conjunction with the observation that P3 does not contribute to HK binding to PPK (25), support the premise that F3 is not involved in HK binding to FXI. Because F3 appears to be important for binding to other components of the coagulation mechanism, such as factor IX (35,45), platelet membranes (51), and heparin (52), it makes sense that it would not be involved in the interaction with HK (43). Taken together, our data are consistent with a model of a discontinuous HK-binding site jointly formed by F2, F1, and F4 of FXI, where domain F2 harbors the core binding sequence and F1 and F4 contribute directly and/or indirectly to this high affinity binding site.…”
Section: Resultsmentioning
confidence: 99%